ChemInform Abstract: A Simple and Efficient Method for the Allylation of Heteroarenes Catalyzed by PdCl2. Issue 1 (3rd January 2013) - Yuan, Feng‐Quan; Sun, Feng‐Yi; Han, Fu‐She
Abstract Various furan, indole and thiophene derivatives are efficiently allylated with several allylic acetates used as an inseparable mixture of regioisomers in the presence of only 2 mol% of PdCl2 under mild conditions.